Effect of Small Private Online Course (SPOC) on students’ achievement in pre-university chemistry - Muhamad Shahbani, Husna Izzati; Abd Rashid, Salleh; Abu Bakar, Muhamad Shahbani; Mohd Jamil, Jastini; Mohd Shaharanee, Izwan Nizal (IJLTER.ORG., 2020)
The COVID-19 outbreak is prompting many public and private universities to abruptly and comprehensively adopt online learning in place of face-to-face classes, to limit transmission of the virus. Academicians, students, and support staff are all working to accommodate this massive change. A survey research on the student, lecturer, and institutional readiness for online learning can help institutions better understand pre-COVID-19 perspectives. This study focuses on a case of Universiti Utara Malaysia (UUM) online education. This paper summary is one of a series of reports outlining higher education's readiness to move teaching and learning online to preserve and continue its educational mission during the current pandemic. Thus, questionnaire is distributed to all lecturers in UUM. The collected data is measured by Likert Scale of 1 to 5 and analyzed using IBM SPSS® software. The overall result has shown that lecturers in UUM are ready for online teaching during the lockdown period. However, there are several issues need to be rectified by the management of the university in preparing lecturer to convert their teaching and learning to online learning. As such, more training is required by the lecturer especially related to technological and online learning tools. Additionally, a reliable online learning platform is a must for the lecturer to endeavor this new experience.